DEKONSTRUKSI CITRA PEREMPUAN PADA LIRIK SATU BULAN DAN KATA MEREKA INI BERLEBIHAN KARYA BERNADYA - Ramadhan Rasyid, Mohammad Ricky (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study analyzes the representation of women's images in two Bernadya songs through the perspective of Simone de Beauvoir's existentialist feminism, especially how women are depicted in patriarchal love relationships. The method used is critical discourse analysis with a hermeneutic approach, examining the hidden meanings behind the language and narrative in the lyrics. Data was obtained from the lyrics of both songs, sourced from credible music platforms, and analyzed based on de Beauvoir's concept of 'the Other.' The findings indicate that women are positioned in a subordinate role, trapped in the effort to achieve perfection in the eyes of their partners, yet never quite sufficient to gain equal recognition. This study contributes to the understanding of gender inequality in popular music media, with implications that music can serve as a tool to explore gendered power imbalances within patriarchal culture.